HIV-exposed uninfected infants’ immune defects: From pathogen sensing, oxidative burst to antigens responses - Joel Fleury Djoba Siawaya; Anicet Christel Maloupazoa Siawaya (iScience, 2023)
Summary: The progress in preventing mother-to-child transmission of HIV has led to a significant reduction in mother-to-child HIV transmission, increasing the population of HIV-exposed uninfected (HEU) infants. Studies have shown that HEU infants are more vulnerable to diseases than infants born from HIV-free mothers. Today, there is more and more evidence that helps us understand how exposure to HIV and/or its therapy affects the ability of the immune system of HEU infants to fight infections. This paper mapped out reported critical immune defects in HEU infants, from pathogen sensing and recognition, oxidative burst to antigens-specific responses. Models of neutrophils and monocyte malfunctions in these infants are proposed.